Modulated electro-hyperthermia therapy combined with Korean mistletoe extract treatment exerts a strong anti-tumor activity by enhancing cellular and humoral immune responses in mice - Yebeen Kim; Jinwoo Hur; Sung-Chul Hong; Jaewoon Jung; Choon-Ho Park; Joon Beom Park; Taek Joon Yoon; Jong Bae Kim; Seung-Hoon Yang (Animal Cells and Systems)
Electro-hyperthermia therapy (EHT) has been known to cause temperature-dependent cell death and enhance the effects of conventional antitumor treatments, such as chemotherapy and radiotherapy. Furthermore, EHT modulates the innate and adaptive immune systems. Mistletoe is one of the most broadly studied complementary and alternative therapeutic agents for cancer treatment due to its ability to stimulate the immune systems. This study aimed to investigate the effects of EHT and mistletoe therapy combination on immune responses. Tumors induced by B16-BL6 melanoma cells were treated twice with modulated EHT (mEHT) (43°C for 10 or 20 min) and with intravenous injection of a Korean mistletoe extract (KME). We examined the level of interferon (IFN)-γ, granzyme, interleukin (IL)-2, IL-10, and tumor-specific antibodies using enzyme-linked immunosorbent assay methods to further study the immunological responses in the combination of mEHT and KME. Additionally, cytotoxic T lymphocyte (CTL) activity is investigated. In this study, we revealed a significant anti-tumor immunological activity elevation in tumor-bearing mice by combined mEHT and KME therapy. Specifically, the combination of mEHT and KME treatment was effective in inhibiting tumor growth in mice. The combination treatment elicited CTL immune response and increased IFN-γ and granzyme secretion. Particularly, the co-treatment appeared to efficiently suppress the immune signal related to tumor-associated macrophage differentiation. Importantly, tumor cell-specific antibodies could be induced in mice after mEHT-treated tumor cell immunization, which represent a promising cancer vaccine strategy. Thus, our results indicate the therapeutic actions of KME as a feasible partner of mEHT, suggesting its potential candidate for cancer immunotherapy.Abbreviations: APC, Antigen-presenting cell; CTL, Cytotoxic T lymphocyte; EHT, Electro-hyperthermia therapy; ELISA, Enzyme-linked immunosorbent assay; HSP, Heat shock protein; KME, Korean mistletoe extract; NK, Natural killer; PBS, Phosphate-buffered saline; QOL, Quality of life; RF, Radio-frequency; TAM, Tumor-associated macrophage